Costs optimisation of reliable self-sufficient electric energy supply at family house. (May 2023) - Čepin, Marko
Highlights: New optimisation algorithm based on new mathematical model of self sufficient electric energy supply (including reliability function). Equations and all parameters suit realistic data, which have obtained accordingly (including the family house consumption data). Results of realistic cases, which suit actual data. Abstract: The objective of the work is to define a method for evaluation of reliable self-sufficient electric energy supply at a family house. The method bases on a mathematical model, which includes electric energy generation in a solar power plant, assessment of realistic electric energy consumption of specified customer and a model of electric battery. The standpoint for evaluation is the equality of electric power production and consumption. Optimisation of costs of energy production from solar power plant and from batteries represents the most important outcome. Realistic time consumption curve of an average family house is determined at every time step, every half an hour based on real consumption. Results include curve of battery state of charge, which confirms the definition of reliability in relation to the size of battery, which is dimensioned in such a manner that its state of charge would never go below zero. The most important result is the optimisation curve of the overall costs of solar power as the primary energy source and battery as the secondary energy source. Minimal costs are identified. Large changes of the results in different years are observed due to different solar radiation in every year and due to different locations.